A fuzzy risk matrix method and its application to the installation operation of subsea collet connector. (January 2017) - Zhang, Kang; Duan, Menglan; Luo, Xiaolan; Hou, Guangxin
Abstract: How to guarantee the successful installation of subsea connectors is an issue that must be solved during offshore operations. Before the subsea connector is installed, it is essential to take appropriate methods to predict the possibility of installation failure, and then safety measures are put forward to reduce the risk of installation failure so as to accomplish the successful installation. In this paper, risk matrix method is adopted to analyze the risk of installation failure event of subsea collet connectors. Accurate values of occurrence probabilities and impact levels of risk factors must be provided in traditional risk matrix analysis, while risk factors in the installation process of subsea connector are lack of these data. To solve this problem, expert evaluation and fuzzy theory are adopted and a fuzzy risk matrix analysis method is formed. Finally, a case study of the installation of a subsea collet connector is carried out. In this study, based on the fuzzy risk matrix method, the installation is successfully guided and conducted. Highlights: A fuzzy risk matrix analysis method model was proposed. Fuzzy theory are adopted to calculate fuzzy failure probability of risk factors. One improved scoring method was introduced to calculate expert weight value. The comprehensive risk rating value of installation failure is calculated to be 1.7. An installation operation test is successfully guided and conducted.